Ion channel expression and function in normal and osteoarthritic human synovial fluid progenitor cells. Issue 2 (3rd March 2016) - Bertram, Karri L.; Banderali, Umberto; Tailor, Pankaj; Krawetz, Roman J.
ABSTRACT: Osteoarthritis (OA) is a chronic disease affecting the cartilage of over 15% of Canadians. Synovial fluid mesenchymal progenitor cells (sfMPCs) are present in joints and are thought to contribute to healing. OA sfMPCs have a greater proliferative ability but decreased chondrogenic potential. However, little is known about the factors influencing/regulating the differences between normal and OA sfMPCs. Recently, our lab has shown that sfMPC chondrogenic differentiation in vitro is favorably biased toward a similar osmotic environment as they experience in vivo . The current study now examines the expression and functionality of a variety of ion channels in sfMPCs derived from normal individuals and early OA patients. Results indicated that there is differential ion channel regulation at the functional level and expression level in early OA sfMPCs. All ion channels were upregulated in early OA compared to normal sfMPCs with the exception of KCNMA1 at the mRNA level. At the protein level, TRPV4 was over expressed in early OA sfMPCs, while KCNJ12 and KCNMA1 were unchanged between normal and early OA sfMPCs. At the functional level, the inward rectifying potassium channel was under expressed in early OA sfMPCs, however the membrane potential was unchanged between normal and early OA sfMPCs. In the synovial environment itself, a number of differences in ion concentration between normal and early OA synovial fluid were observed. These findings suggest that normal and OA progenitor cells demonstrate functional differences in how they interact with the synovial ion environment.